No More Vietnams - Nixon, Richard M. 1913-1994 (London W.H. Allen, 1986)
The late president provides his explanation of America's failure in the Vietnam conflict and argues that the U.S. should not allow its foreign policy to be paralyzed by fear of another Vietnam.
Keywords: Vietnam War (1961-1975) -- Developing countries